La guerre, des lieux et des noms. L’Ukraine à l’heure de la décommunisation - Alexia Kis-Marck (Lengas)
In this contribution, we address the decommunization policy reestablished in Ukraine in 2015 and its specific implementation by the renaming of street and city names. In particular, we investigate how place names served the process of national identity reconstruction of this war-torn country, mainly to rebuild their historic and collective memory. We focus more specifically on the case of the city of Dnipro and of its streets renaming process, namely by interviewing its population. An attempt is made to assess the inhabitants’satisfaction, tolerance or resistance to the renaming process taking place in their city and to show how their attitudes towards the new street names reflect their way of experiencing the ongoing conflict and the new Ukrainian politics.